Cyber Risk, Market Failures, and Financial Stability - Kopp, Emanuel; Kaffenberger, Lincoln; Wilson, Christopher (Washington, D.C. : International Monetary Fund, 2017)
Cyber-attacks on financial institutions and financial market infrastructures are becoming more common and more sophisticated. Risk awareness has been increasing, firms actively manage cyber risk and invest in cybersecurity, and to some extent transfer and pool their risks through cyber liability insurance policies. This paper considers the properties of cyber risk, discusses why the private market can fail to provide the socially optimal level of cybersecurity, and explore how systemic cyber risk interacts with other financial stability risks. Furthermore, this study examines the current regulatory frameworks and supervisory approaches, and identifies information asymmetries and other inefficiencies that hamper the detection and management of systemic cyber risk. The paper concludes discussing policy measures that can increase the resilience of the financial system to systemic cyber risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet